A culturally informed approach to mental toughness development in high performance sport - Eubank, U.; Nesti, M.; Littlewood, M. (International Journal of Sport Psychology, 2017)
The purpose of the current paper is to explore the importance of culture in the development of Mental Toughness (MT). This is done by means of a critical review of the current literature that exists in relation to the conceptualisation, definition and development of the concept. We argue that despite recent advances in our understanding, most research into MT has focused on the characteristics of mentally tough individuals. Although important and useful, the role of the environment (e.g., Bull et al. 2005; Hardy et al. 2015), culture (e.g., Tibbert et al. 2015), and context (e.g., Fawcett 2011), and how these impact MT and its development has been given somewhat less attention and is perhaps not well integrated into practice. This relative oversight has occurred because of three specific issues; an exclusive focus on the individual; a top down approach to research and the conceptualisation of MT; a lack of awareness that the athlete is always located in a specific organisation and sport culture with its own processes, systems, values and beliefs. In order to more fully capture how MT is constituted and developed, we suggest that future research needs to adopt a wider perspective by drawing on work around the importance of culture in sport, and make greater use of qualitative methodologies, such as grounded theory, narrative, ethnography and phenomenology to capture the culturally rich accounts of participants. Such a shift, as advocated in this paper, provides a primary point of reference to offer fresh insight in our research efforts, and will also have a major influence on practitioner development and training to assist applied sport psychologists and coaches in the practical task of building and supporting MT development in athletes.